2019
DOI: 10.4067/s0718-58392019000100089
|View full text |Cite
|
Sign up to set email alerts
|

HortSyst: A dynamic model to predict growth, nitrogen uptake, and transpiration of greenhouse tomatoes

Abstract: The HortSyst model is a new discrete time model for describing the dynamics of photo-thermal time (PTI), total dry matter production (DMP), N uptake (Nup), leaf area index (LAI), and evapotranspiration (ETc) for greenhouse crops. The first three variables are considered as state variables and the latter two are conceptualized as output variables. This model was developed as a tool for decision support systems in Mexican greenhouses for the application of N and water in tomato (Solanum lycopersicum L.) producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In these conditions, environmental control and growth techniques are commonly used to optimize biomass production of crops. Therefore, it is important to measure the crop weight, which is an indicator of biomass production itself and is used as a key parameter for crop growth models [7][8][9][10]. Manual measurements are the most common method to determine crop weight.…”
Section: Introductionmentioning
confidence: 99%
“…In these conditions, environmental control and growth techniques are commonly used to optimize biomass production of crops. Therefore, it is important to measure the crop weight, which is an indicator of biomass production itself and is used as a key parameter for crop growth models [7][8][9][10]. Manual measurements are the most common method to determine crop weight.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have concluded that grafting can increase chlorophyll content and leaf area of plants, thereby increasing plant photosynthesis (Khah, 2011;Haberal et al, 2016). The developed roots have a larger rootshoot ratio and a stronger ability to absorb nutrients, thereby increasing the photosynthesis rate and chlorophyll content (Martínez-Ruiz et al, 2019). In this experiment, several graft combinations increased the chlorophyll content and the absorption of mineral elements of tomato.…”
Section: Discussionmentioning
confidence: 64%
“…The dynamic HORTSYST model proposed by Martinez-Ruiz et al [21] assumes no water and nutrient constraints (potential growth or potential biomass production) on the crop, and it simulates photo-thermal time (PTI, MJ d −1 ), dry matter production (DMP, g m −2 ), and nitrogen uptake (Nup, g m −2 ) as the state variables, while the leaf area index (LAI, m 2 m −2 ) and crop transpiration (ET c , kg m −2 ) are considered as output variables. The model structure is summarized in Table 1.…”
Section: Model Descriptionmentioning
confidence: 99%
“…HORTSYST is a new model that describes nonlinear dynamic systems, and it simulates output variables, such as photo-thermal index (PTI), dry matter production (DMP), leaf area index (LAI), nitrogen uptake (Nup), and crop transpiration (ET c ) [21]. The HORTSYST model is a crop growth model that considers input variables that can usually be measured without any problem inside a greenhouse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation